Análise do apoio dos sistemas de informação para as práticas de gestão ambiental em empresas com ISO 14001 - estudo de múltiplos casos - Fiorini, Paula De Camargo [UNESP]; Jabbour, Charbel Jose Chiappetta [UNESP] (Escola de Ciência da Informação da UFMG, 2014)
The purpose of this article is to identify the contributions of Information Systems (IS) for environmental management practices, as well as the opportunities and challenges in this relation. Thus, we performed two case studies with Brazilian enterprises certified ISO 14001, by conducting interviews, document analysis and direct observation. As results, we present the identification of the main contributions of information systems for environmental management practices in the studied cases, the verification that a more advanced stage regarding IS is a factor that implies a more effective contribution, besides finding challenges and opportunities in this relation. The main contribution of this research consists of the presentation of a framework that identifies the support of information systems for environmental practices.

O objetivo deste artigo é identificar as contribuições dos Sistemas de Informação (SI) para as práticas de gestão ambiental, bem como as oportunidades e desafios na relação entre ambos. Para tanto, foram realizados dois estudos de caso com empresas brasileiras certificadas ISO 14001, através da condução de entrevistas, análise documental e observação direta. Como resultados, apresentam-se a identificação das principais contribuições dos sistemas de informação para as práticas de gestão ambiental nos casos estudados, a verificação de que um estágio mais avançado em relação aos SI é um fator que implica em uma contribuição mais efetiva, além da constatação de desafios e oportunidades nessa relação. A principal contribuição desta pesquisa consiste na apresentação de um framework, que identifica o apoio dos sistemas de informação às práticas ambientais.
Analysis of support of information systems for environmental management practices in enterprises with ISO 14001: a multiple case study
Keywords: Sistemas de informação; Gestão ambiental; ISO 14001; Práticas ambientais; Information systems; Environmental management; ISO 14001; Environmental practices